Soviet Documentary Films in Lithuania: Historical and Ideological Contexts (1963–1988) - Černeckaitė, Irina (Genocidas ir rezistencija, 2005)
The entire cinematography and documentary film production of the Soviet Union often created an analogue a country leading an autonomous life on the screen. It sought to integrate society by spreading Communist ideology and maintaining the vision of social order and progress.Based on interviews from the respondents who had worked in various cinematographic institutions in Soviet Lithuania, this article presents a structural analysis of the documentaries, with emphasis on the film-making processes.The high noon of the Lithuanian documentaries of the sixties was determined by interesting processes and falls within the general dynamics of the production of documentary films in the Soviet Union, the socialist East European block and in the Western world. As the research has revealed, the strenuous implementation of agitation-propaganda, the educational and cultural tasks of the regime were due to both political changes in the Soviet Union, the country's ideological doctrine and social-cultural processes, as well as internal factors which then existed in cinematography – protecting one self, a wish to represent the "positive" sides of life in the republic, and the personal likings and points of view of the censors. All this determined the methodology of "approving" and "correcting-cutting" the films.While analysing the structural documentary film-making process systematically, it is possible to assume that the system of the regime's directives and the approval of films operated on the principle of keeping a balance with the Party line.
Keywords: art; culture; cinema; Soviet culture; communist ideology